Pengaruh Penerapan Video Pembelajaran Interaktif Terhadap Hasil Belajar pada Mata Pelajaran IPS Kelas VIII di SMPN 1 Kubung - Zaini, Qori Aprilia; Ikhwan, Ikhwan; Zora, Fera (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the low learning outcomes of class VIII students in social studies at SMPN 1 Kubung, this is because teachers have not used interactive learning videos optimally in following the learning. This study aims to determine. The effect of the application of interactive learning videos on learning outcomes of class VIII in social studies at SMPN 1 Kubung. This type of research is quantitative research. The population in the study were students of class VIII.1, VIII.2, and VIII.3 at SMPN 1 Kubung in the 2024/2025 academic year, namely 81 people. Sampling was carried out using a total sampling technique of 81 people. The analysis technique used is a simple linear regression analysis technique, and the data collection techniques used are observation, questionnaires, and questionnaires. The results of this study indicate that interactive learning videos on learning outcomes value (Sig) 0.00 <0.05 and the t count value> t table (3.591> 1.667) means that H_a is accepted and H_o is rejected. Based on the results, it can be concluded that there is a positive and significant influence of the implementation of interactive learning videos on the learning outcomes of eighth-grade students in social studies at SMPN 1 Kubung. It is recommended that teachers continue to provide guidance on the use of interactive videos to help resolve learning difficulties experienced by students